RANCANG BANGUN PURWARUPA PALANG PERLINTASAN KERETA API OTOMATIS DENGAN IOT BERBASIS ARDUINO PRO MINI - Purnama Yudha, I K A S; Hakim, M Z; Raka Agung, I G A P; Sukadarmika, Gede (Jurnal SPEKTRUM; Vol 11 No 3 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i03.p1, 2024)
The development of automatic railway crossing bars based on the Internet of Things (IoT) plays a role in improving safety and reducing the risk of accidents around railway crossings. Automatic railway crossing crossings have monitors of train status, current, voltage and power. The monitor uses an arduino pro mini module, ESP32 as well as receiver sensor components, KY – 008 laser sensor, ACS712 current sensor, ZMPT101B voltage sensor, RTC, 5 Volt DC stepper motor, ULN2003 driver, buzzer and red LED. The materials and tools used support design methods such as overview, hardware blocks, software, mechanical structures and prototype testing. The research uses testing methods to obtain primary and secondary data obtained from data sheets, journals, articles and books. This study is useful for pedestrians who cross pedestrian paths on railway crossing bars and vehicles that cross railway crossing bars. Data obtained from the status monitor of the crossing bar and the electrical prototype stated that the implementation of the prototype hardware of the railway crossing bar was successful. The implementation of the software has been prototyped and can be monitored by the Antares and Telegram platforms. Prototype work gets a compatibility between hardware and software.